Vitamin D Represses the Aggressive Potential of Osteosarcoma - Tahbazlahafi, Behnoosh; Paknejad, Malihe; Khaghani, Shahnaz; Sadegh-Nejadi, Sahar; Khalili, Ehsan (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Osteosarcoma (OS) is the basic bone neoplasm with lower survival and poor prognosis. It is distinguished by its offensive nature and metastatic potential. The fundamental death source in OS patients is lung metastasis. In addition, the proliferation and cell migration are thus essential for cancer progression, especially for intrusion and transformation. Several studies have illustrated that 1,25-Dihydroxyvitamin D (1,25(OH)2D) has a critical role in the growth and differentiation of bone. However, knowledge of the outcome of 1,25(OH)2D on the progression and incursion of osteosarcoma cells is minimal. Objective: The present study aimed to analyze the effect of different concentrations of 1,25(OH)2D on the multiplication, progression, and intrusion of OS cells and verify the effective doses of 1,25(OH)2D that can decrease the intensity of the disease and improving the prognosis in OS patients. Methods: Saos-2 cells were treated with 1,25(OH)2D (0, 50, 100, and 200 nM) for 48, 72, and 96 hours. Proliferation, invasion, and migration were determined by MTT assay, Transwell assay, and Scratch test, respectively. The levels of c-Myc and FOXO1 proteins were determined by Western blotting. Results: The proliferation, invasiveness, and migration of Saos-2 cells that were treated with 1,25(OH)2D were significantly decreased compared with untreated cells. Although 1,25(OH)2D notably decreased c-Myc protein levels (after 48 and 72 hours), FOXO1 protein levels have been significantly increased after 48 and 72 hours. 1,25(OH)2D and the vitamin D receptor (VDR) suppress c-Myc function through regulating the c-Myc/MXD1 network and thus, providing a molecular basis of 1,25(OH)2D related to the cancer-preventive actions. Conclusion: Based on the present results, 1,25(OH)2D by targeting c-Myc and FOXO1 expression displays anti-invasive, anti-migration and anti-proliferative effects on OS cells in vitro. Our findings suggest that effective doses of the 1,25(OH)2D may reduce the aggressive potential of the OS cell line. However, further investigation and clinical trials are needed.
Keywords: in vitro